The grammar of traditional Malay long-roof type houses - Said, Suzana (2007)
In this paper, the grammar of the traditional Malay houses (TMH) built in the past century is presented. The basic unit structures that form the shape of the TMH are first derived. Evidences of the basic unit structures or their combinations were documented by previous researchers and are used as a way of explaining the physical, spatial and functional relationships of the built forms of the TMH. The scope of the study is currently limited to the original TMH of the bumbung panjang (long roof) type in which the key features of the houses were easily discernible from the side view. The shape addition rules for generating these structures are used to characterize the compositional aspects of TMH style.